Adipocyte OGT governs diet-induced hyperphagia and obesity - Min-Dian Li (Nature Portfolio, 2018)
Endocannabinoid signaling regulates food intake and is a potential therapeutic target for obesity. Here the authors show that adipocyte O-GlcNAc transferase (OGT) is required for high fat diet-induced hyperphagia via transcriptional activation of de novo lipid desaturation and accumulation of an endogenous appetite-inducing cannabinoid.